2006
DOI: 10.1213/01.ane.0000208966.24695.30
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of Arterial Po2 Oscillations for Conventional Arterial Blood Gas Analysis

Abstract: In a surfactant-depletion model of lung injury, tidal recruitment of atelectasis and changes in shunt fraction lead to large Pao2 oscillations. We investigated the effect of these oscillations on conventional arterial blood gas (ABG) results using different sampling techniques in ventilated rabbits. In each rabbit, 5 different ventilator settings were studied, 2 before saline lavage injury and 3 after lavage injury. Ventilator settings were altered according to 5 different goals for the amplitude and mean valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 21 publications
0
27
1
2
Order By: Relevance
“…The saline lavage model replicates the surfactant dysfunction of ARDS (34,70), but other features such as epithelial and endothelial damage and alveolar inflammation take several hours to develop after lavage (41,59). Our model of mild injury with surfactant depletion in mature lungs is most likely relevant to early stages of injury in patients at risk for development of ARDS and ALI (52,57,70).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The saline lavage model replicates the surfactant dysfunction of ARDS (34,70), but other features such as epithelial and endothelial damage and alveolar inflammation take several hours to develop after lavage (41,59). Our model of mild injury with surfactant depletion in mature lungs is most likely relevant to early stages of injury in patients at risk for development of ARDS and ALI (52,57,70).…”
Section: Discussionmentioning
confidence: 79%
“…Whether collapse occurs at a particular end-expiratory pressure depends not just on that pressure and the volume history, but also on how long the airway has remained at that pressure (5). Several methods that have the potential to directly assess cyclical recruitment have been applied in recent research studies, including electrical impedance tomography (15,32,71), dynamic CT (39,40,46,47,71), subpleural vital microscopy (24, 65), rapid continuous Pa O 2 monitoring (5), timed blood gas collection (52), and fast pulse oximetry (66). None of these methods have been used, however, to study the dynamics of end-expiratory collapse in ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent alveolar derecruitment throughout the apnea (10,35) and to match lung volume during the 13 N 2 scan, at which regional shunt was measured, with mean lung volume during the transmission scan, at which aeration was measured, apnea was performed at an airway pressure equal to mean airway pressure during breathing. Blood gas samples were drawn over two respiratory cycles to minimize variability due to sample timing (11). Accordingly, measurements of shunt and aeration should reflect the physiologic condition of the lung at approximately mean lung volume and be comparable to measurements of lung density obtained by averaging dynamic CT frames over consecutive respiratory cycles (42,43).…”
Section: Rationale and Critique Of The Experimentsmentioning
confidence: 99%
“…Because Pa O 2 varies during the respiratory cycle in the acutely injured lung (10,11), lack of synchrony between the phases of the cycle at which lung density and blood gases are measured is expected to introduce spurious variability in the relation between shunt fraction and lung aeration. Another possible explanation is that measurements of regional density do not take into account the effect of the regional distribution of perfusion on gas exchange.…”
mentioning
confidence: 99%
“…In fact, at the moment, a routine method to assess cyclical recruitment at bedside is not available. It has been suggested that the monitoring of time-dependent intra-arterial oxygen tension oscillations may reflect this phenomenon, as shown in surfactant-depleted ventilated rabbits [22,23]. This method, however, requires the use of a probe inserted in the distal aorta.…”
Section: Pulse Oximetrymentioning
confidence: 99%